2014
DOI: 10.3389/fnbeh.2014.00109
|View full text |Cite
|
Sign up to set email alerts
|

Learned helplessness and social avoidance in the Wistar-Kyoto rat

Abstract: The Wistar-Kyoto (WKY) rat is an established depression model characterized by elevated anxiety- and depression-like behavior across a variety of tests. Here we further characterized specific behavioral and functional domains relevant to depression that are altered in WKY rats. Moreover, since early-life experience potently shapes emotional behavior, we also determined whether aspects of WKYs' phenotype were modifiable by early-life factors using neonatal handling or maternal separation. We first compared WKYs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
99
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 102 publications
19
99
1
Order By: Relevance
“…More promising are Wistar-Kyoto rats, which were originally bred as a normotensive control strain for the spontaneously hypertensive (SHR) rat strain, but were later found to display physiological and behavioural features suggestive of heightened emotionality, including increased immobility in the FST (Nam et al 2014) and, of greater relevance, enhanced physiological responses to repeated stress (Morilak et al 2005) and an increased propensity to develop LH (Belujon and Grace 2014). Strain differences in antidepressant responses have not been studied in relation to LH, but WKY rats have been shown repeatedly to be less responsive to antidepressants in the FST, with some studies reporting a specific sub-sensitivity to serotonergic antidepressants (López-Rubalcava and Lucki 2000) and others reporting a more general effect (Lahmame et al 1997).…”
Section: Personality Factorsmentioning
confidence: 99%
“…More promising are Wistar-Kyoto rats, which were originally bred as a normotensive control strain for the spontaneously hypertensive (SHR) rat strain, but were later found to display physiological and behavioural features suggestive of heightened emotionality, including increased immobility in the FST (Nam et al 2014) and, of greater relevance, enhanced physiological responses to repeated stress (Morilak et al 2005) and an increased propensity to develop LH (Belujon and Grace 2014). Strain differences in antidepressant responses have not been studied in relation to LH, but WKY rats have been shown repeatedly to be less responsive to antidepressants in the FST, with some studies reporting a specific sub-sensitivity to serotonergic antidepressants (López-Rubalcava and Lucki 2000) and others reporting a more general effect (Lahmame et al 1997).…”
Section: Personality Factorsmentioning
confidence: 99%
“…In the behavioral tasks for which the level of difficulty was increased, the WKY rats exhibited severe stress responses, increased freezing behavior and reduced activity [27]. Additionally, the WKY rats clearly showed diminished movement across the multiple behavior tests relative to the W rats, indicating a certain degree of behavioral inhibition and psychomotor retardation as a result of increased stress [6]. In our previous work, we did not observe changes in the rewarding effects of cocaine during the acquisition/maintenance of cocaine self-administration in OBX rats [3] Therefore, this result may suggest that the abnormalities are specific to the WKY strain, as a consequence of their predisposition to exhibit anxiety-like behavior [28].…”
Section: Behavioral Experimentsmentioning
confidence: 96%
“…One theory used to explain the frequent co-occurrence of these two disorders is the self-medication hypothcocaine self-administration model in Wistar Kyoto (WKY) rats, which are prominently and frequently used as a rodent model of depression [4,5]. WKY rats display depression-like behavior in a wide range of behavioral paradigms, characterized by a high level of immobility in the forced swim test (FST), greater social avoidance [6], reduced activity in open field tests [7], and diminished activity in novel environments [8][9][10]. Recent studies have also indicated that WKY rats exhibit a 50% increase in paradoxical sleep during the normal sleep phase and increased sleep fragmentation [11].…”
Section: Introductionmentioning
confidence: 99%
“…Immobility during the FST has been generally interpreted as a result from despair or depression [35]. However, it could also be interpreted as a development of the relatively successful coping strategy that employs energyconserving behavior based on learning and memory, rather than simply despair-based depression [36,37]. Therefore, the results of the FST in the BCCAo rats with an underlying cognitive impairment need to be interpreted in both aspects: despair and depression versus learning and memory.…”
Section: Depressive-like Behaviors In a Rat Model Of Chronic Cerebralmentioning
confidence: 97%